National Culture and the Model of Business Organization for the Case of Kosovo - Terziu, Hysni (European Journal of Economics and Business Studies, 2016)
The study of culture of businesses is important for the requirements that today the globalization sets. While the expending of business across borders is becoming more and more common, the national challenges are becoming more and more present. The underestimation of all these trends and their relationship to the culture may a reason for the increase of the number of existing or even of new businesses. The research aims at explaining at how have changed the dimensions of national culture during the initial years of transition and during the continues years. Which are the new values that dominate the business activities in Kosovo? Can we admit that the new values determine the models for activity coordination? The article provides an overview of the dimensions of culture as a determinant of the type of organization. It aims to show the approximate positioning in these structuring forms. The modeling shows at modest way the competitive advantages that the culture offers. The economic contribution of culture shows how should be the models for cordinating the activities which will be the trend in the future. The Twenty-first century is putting Kosovo businesses in front of new perspectives and new challenges, which are added to existing ones and which are becoming even more acute. These all seek even more the attention of their managers. The purpose of this paper is to provide an insight on how to be organized from the structural and human aspect in order to react according to the culture in many organizations with new innovative ideas, in accordance to the requirements of the time in order to have an effect on the social system, on lifestyle, on economic system and on the organization of units in this system. All these help on the definition of basic models of organizations with a strategic planning as a condition for intercultural integration and coordination - national and international.